Enhancing Communication Skills of Individuals With Autism Spectrum Disorders While Maintaining Social Distancing Using Two Tele-Operated Robots - Kumazaki, Hirokazu; Muramatsu, Taro; Yoshikawa, Yuichiro; Haraguchi, Hideyuki; Sono, Taichi; Matsumoto, Yoshio; Ishiguro, Hiroshi; Kikuchi, Mitsuru; Sumiyoshi, Tomiki; Mimura, Masaru (Frontiers in Psychiatry, 2021)
COVID-19 has affected many areas of daily life, including communication and learning. Social distancing is essential to prevent the spread of COVID-19. In these situations, teaching communication skills is essential for helping individuals with autism spectrum disorders (ASD) reach their full potential. To provide communication education while maintaining social distancing, we developed a communication training system using a tele-operated robot. In this system, we prepared a PC and a robot for each participant. The participants were grouped in pairs and communicated with each other through the tele-operated robot. The objective of this study was to test whether this system can maintain motivation for training in individuals with ASD and whether our system was useful for improving communication skills. Participants were randomly assigned to one of two groups: the taking a class by teachers alone (TCT) group or robot-mediated communication exercise (RMC) group. Participants in the TCT group took a class about communication skills from their teacher. Participants in the RMC group, in addition to taking a class by teacher, were grouped in pairs and communicated with each other through the tele-operated robot once a week over four weeks (for a total of 5 sessions). In total, twenty individuals with ASD participated in the study. One-way ANOVA revealed that there were significantly greater improvements in being good at describing their thoughts to others, which was self-rated (F = 6.583; p = 0.019), and good at listening to the thoughts or feelings of others, which was rated by themselves (F = 5.635; p = 0.029) and their teacher (F = 5.333; p = 0.033). As expected, the motivation for training using this system was maintained during a session. Overall, this study revealed that our system was useful for improving communication skills (e.g., listening to the thoughts or feelings of others). Teaching communication skills under pandemic conditions is important, and this study demonstrated the feasibility of communication training using tele-operated robots.